Analysis of Amino Acids Network Based on Nucleotide of DNA - Sharma, Sanjay; Boruah, Birinchi Kumar; Ali, Tazid (Communications in Mathematics and Applications, 2023)
The sequence of amino acids in protein synthesis is determined by the order of monomers of DNA. A study on the physicochemical aspect of nucleotide of DNA gives us valuable characteristics related to amino acids and protein functions. We considered six different parameters for four nucleotide of DNA and weighing each of them we constructed a distance matrix for twenty amino acids and subsequently, an amino acids network. In this network, we looked into evolutionary pattern of amino acids based on nucleotide of DNA and how it plays significant roles in the function of protein stability and membrane proteins. Lastly, we investigate several centrality metrics and explored correlation coefficients to assess the network’s assortativity for a comparative analysis of amino acids. We have also examined the clustering coefficient, degree distribution, and skewness as network parameters.